Advances in Cardiovascular Surgery Techniques - Jacobson, Anne (MD Conference Express, 2007)
Cardiovascular surgery is becoming less invasive, more focused, and safer, according to speakers who presented new approaches to several traditional surgical procedures. This article discusses hybrid revascularization for coronary artery disease, transapical aortic valve replacement, and atrial fibrillation ablation.